Bidirectional Visible Light Communication System Using a Single VCSEL With Predistortion to Enhance the Upstream Remodulation - Liang-Yu Wei; Chi-Wai Chow; Chin-Wei Hsu; Chien-Hung Yeh (IEEE Photonics Journal, 2018)
The demand of higher data rates has made it attractive to consider a low-cost laser diode (LD), such as vertical-cavity-surface-emitting laser (VCSEL) for use in visible light communication (VLC) transmitters (Tx) due to their higher electrical-to-optical modulation bandwidth, beam convergence, and energy efficiency. Many reported LD-based VLC systems only had a solitary downstream transmission. We demonstrate a 3-m bidirectional signal remodulated VCSEL-based VLC system using visible-light modulator to produce the upstream signal. The visible-light external modulator usually has limited modulation bandwidth. By using the predistortion, the upstream remodulated data rate is enhanced by ∼2.8 times. Hence, the VCSEL-based VLC system with 10.64-Gb/s downstream signal and 5-Mb/s upstream remodulated signal can be achieved. We also analyze via numerical simulations how the predistorted signal can enhance the transmission data rate by mitigating the intersymbol interference introduced by the bandwidth limitation of the upstream modulator.